Preliminary Study of the Influence of Post Curing Parameters to the Particle Reinforced Composite's Mechanical and Physical Properties - Aare ARUNIIT; Jaan KERS; Andres KRUMME; Triinu POLTIMÄE; Kaspar TALL (Medžiagotyra, 2012)
This study examines the effect of different post cure parameters to a polymer matrix particulate reinforced composite material. The goal is to evaluate the importance of different factors and to suggest a well-balanced post cure mode that supports the application of the material. Polymer matrix composites are post cured at elevated temperature to increase the amount of cross linking to achieve better chemical and heat resistance and mechanical properties. Every material has an individual post cure process that depends from the raw materials. Post curing variables include temperature, duration of cure, the time between initial curing and post curing and temperature profile gradient. There are several ways to determine the cure state of a polymer. It can be evaluated based on the mechanical and physical properties, residual styrene content, glass transition temperature, residual exotherm or solvent swelling test. For the determination of the suitable post cure parameters test slabs were casted and post cured with varying time and temperature. Glass transition temperature, residual exotherm, softening in ethanol, surface hardness, flexural strength and flexural modulus were determined. It is shown that the material should be cured at 60 °C – 80 °C. With higher temperature and extended time of cure the glass transition temperature raises but the material becomes too brittle. DOI: http://dx.doi.org/10.5755/j01.ms.18.3.2435